E-learning in art and design : perceptions and practices of lecturers in undergraduate studio-based disciplines and the rhetoric of innovative practices - Souleles, Nicos (My University, 2011)
The objective of this research is to compare the noticeably prevalent perception among undergraduate studio-based art and design lecturers that elearning can contribute little or nothing to teaching and learning, against the rhetoric and literature of elearning associated with competencies for the knowledge economy. The inference is that elearning is unsuitable for the instructional strategies associated with art and design education. This anecdotal evidence together with the limited studies on the implementation of online learning technologies in art and design education, triggered this research. The significance of this study is that it seeks to contribute to the present re-evaluations of art and design education in the context of the knowledge economy. The core question is: how do the perceptions and practices of teaching staff in art and design disciplines compare and contrast with the associated rhetoric and literature of elearning and innovative practices? Consistent with the phenomenographic approach to research, this study pursues a second-order perspective, i.e. through a qualitative analysis of interviews this research deals with people’s experiences of aspects of the world. It considers the pedagogies associated with elearning for the premise is that the competencies required for the knowledge economy cannot be provided for unless there is a corresponding change in teaching and learning methods. This research confirms the prevalence of the perception that elearning can contribute little or nothing to teaching and learning and attributes this to the historical evolution of art and design pedagogies, the persistence of didactic methods, the false understanding of elearning as replacing rather than enhancing teaching and learning practices and the lack of sufficient and appropriate professional development and training opportunities for teaching staff. The implication is that there is a noticeable misalignment between perceptions and practices of elearning and the associated rhetoric and literature of elearning and innovative teaching and learning practices.
Keywords: Art and design; Teaching; Learning; Knowledge economy